A brief culturally tailored intervention for Puerto Ricans with type 2 diabetes. - Osborn, Chandra Y; Amico, K R; Cruz, Noemi; O'Connell, Ann A; Perez-Escamilla, Rafael; Kalichman, Seth C; Wolf, Scott A; Fisher, Jeffrey D (Health education & behavior : the official publication of the Society for Public Health Education, 2010)
The information-motivation-behavioral skills (IMB) model of health behavior change informed the design of a brief, culturally tailored diabetes self-care intervention for Puerto Ricans with type 2 diabetes. Participants (n = 118) were recruited from an outpatient, primary care clinic at an urban hospital in the northeast United States. ANCOVA models evaluated intervention effects on food label reading, diet adherence, physical activity, and glycemic control (HbA1c). At follow-up, the intervention group was reading food labels and adhering to diet recommendations significantly more than the control group. Although the mean HbA1c values decreased in both groups (Intervention: 0.48% vs. Control: 0.27% absolute decrease), only the intervention group showed a significant improvement from baseline to follow-up (p < .008), corroborating improvements in diabetes self-care behaviors. Findings support the use of the IMB model to culturally tailor diabetes interventions and to enhance patients' knowledge, motivation, and behavior skills needed for self-care.
Keywords: Age Factors; Aged; Cultural Competency; Diabetes Mellitus, Type 2; Diet; Exercise; Female; Food Labeling; Health Behavior; Health Education; Health Knowledge, Attitudes, Practice; Hemoglobin A, Glycosylated; Hispanic Americans; Humans; Male; Middle Aged; Motivation; Puerto Rico; Self Care; Sex Factors; Socioeconomic Factors